ECTOPIC ENTEROBIUS VERMICULARIS INFESTATION; AN EXTREMELY RARE CAUSE OF MESENTERIC LYMPHADENOPATHY MIMICKING TUBERCULOUS LYMPHADENITIS - Zafar, Summaya; Tariq, Muhammad Usman; Ahmed, Zubair (Journal of Ayub Medical College Abbottabad, 2018)
Enterobius vermicularis (EV) is a pinworm which commonly resides in the lumen of the intestinal tract and lays eggs on the perianal skin. However, rarely the worm can infest various other sites in the body and cases with infestation of such ectopic sites have been reported in literature. Rare cases of mesenteric lymph node involvement have also been reported. We report a case in a young male who presented with signs and symptoms of acute appendicitis. During surgery, enlarged mesenteric lymph nodes were identified. Histological examination revealed adult worm in the appendiceal lumen. Histological examination of mesenteric lymph node revealed degenerated worm surrounded by caseating chronic granulomatous inflammation. We conclude that EV infestation should be considered in the differential diagnosis of enlarged mesenteric lymph node with chronic granulomatous inflammation, especially in young patients and when accompanying bowel tissue also reveal the helminth. Keywords: Enterobius vermicularis; Mesenteric Lymphadenopathy; Acute Appendicitis; Ectopic